A response to COVID‐19 school closures: The feasibility of a school‐linked text message intervention as an adaptation to school‐supervised asthma therapy. Issue 5 (16th February 2022) - Arenas, Juliana; Becker, Sarah; Seay, Hannah; Frisard, Christine; Hoque, Shushmita; Spano, Michelle; Lindenauer, Peter K.; Sadasivam, Rajani S.; Pbert, Lori; Trivedi, Michelle
Abstract: Background: School‐supervised asthma therapy improves asthma medication adherence and morbidity, particularly among low‐income and underrepresented minority (URM) children. However, COVID‐19‐related school closures abruptly suspended this therapy. In response, we developed a school‐linked text message intervention. Objective: The purpose of the study is to investigate the feasibility and acceptability of a school‐linked text message intervention. Methods: In December 2020, children previously enrolled in school‐supervised asthma therapy in Central Massachusetts were recruited into this school‐linked text message intervention. We sent two‐way, automated, daily text reminders in English or Spanish to caregivers of these children, asking if they had given their child their daily preventive asthma medicine. Our study team notified the school nurse if the caregiver did not consistently respond to text messages. School nurses performed weekly remote check‐ins with all families. The primary outcome of the study was feasibility: recruitment, retention, and intervention fidelity. Secondarily we examined intervention acceptability and asthma health outcomes. Results: Twenty‐six children (54% male, 69% Hispanic, 8% Black, 23% White, 93% Medicaid insured) and their caregivers were enrolled in the intervention with 96% participant retention at 6 months. Caregiver response rate to daily text messages was 81% over the study period. Children experienced significant improvements in asthma health outcomes. The intervention was well accepted by nurses and caregivers. Conclusion: A school‐linked text messaging intervention for pediatric asthma is feasible and acceptable. This simple, accessible intervention may improve health outcomes for low‐income and URM children with asthma. It merits further study as a potential strategy to advance health equity.